Evaluation of anti-diabetic properties of cosmos caudatus kunth leaves in obese-diabetic induced rat using metabolomics approach - Khatib, Alfi; Perumal, Vikneswari; Abdul Hamid, Azizah; Abas, Faridah; Khozirah Saari, Intan; Ismail, Safinar; Ismail , Amin (2014)
Diabetes mellitus prevalence is increasing rapidly worldwide. It is resulted from the combination of impaired insulin secretion with reduced insulin sensitivity of the target tissues. The objective of this study is to evaluate metobolites profile in the serum of rats in different conditions (healthy, diabetes, Cosmos caudatusand metformin treated) using NMR based-metabolomics approach. The 80 % ethanol extract of C. caudatus was force fed to diabetic rats. Streptozotocin was used to induce the obese rat to become diabetic (ob-db). Rats were divided into four groups: healthy rat, ob-db treated with 300 mg/kg metformin and ob-db treated with 200 mg/kg of C. caudatus. The NMR spectrum of serums were statistically calculated using multivariate data analysis to discriminate the groups and to identify the metabolites responsible for discrimination. Glucose level which was elevated in diabetic rats can be reduced to the normal range after metformin and C. caudatus treatment. Interestingly metformin caused elevation of ethanol, lactate and alanine which were not observed in C. caudatus treated rats. Other significant metabolites which have been identified were glucose, ethanol, alanine and lactate. This study suggested that C. caudatus has potential for the treatment of diabetes.